TANTANGAN GURU DALAM MENINGKATKAN PERKEMBANGAN LITERASI AWAL ANAK DALAM KONTEKS PEMBELAJARAN DEEP LEARNING DI PENDIDIKAN DASAR: ANALISIS KASUS KESULITAN PENGENALAN HURUF - Muhajanah; Berlian Adi Nugroho; Indah Lestari; Moch.Widjanarko (STKIP Subang, 2025)
This research analyzes the challenges teachers face in enhancing early literacy development among elementary school students within the context of deep learning pedagogy, focusing on a case study of letter recognition difficulties. Conducted at SD Negeri 3 Tempur, this qualitative case study examines a first-grade student who demonstrates an atypical literacy profile: the ability to